Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Informasi Akuntansi Pada Usaha Kecil Dan Menengah Batik Di Kota Pekalongan - Khusnalibah Khusnalibah; Janti Soegiastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of education, business scale, work motivation, length of business life and accounting training on the use of accounting information. This research was conducted by distributing questionnaires to Micro, Small and Medium Enterprises (MSMEs) in South Pekalongan District, Pekalongan City. With a population of 126 and samples taken using the saturated census method were 126 MSMEs. The data collection method in this research used a questionnaire. The results of this research show that Business Scale (X2) and Work Motivation (X3) have a significant positive effect on the use of accounting information in District MSMEs, while Education (X1), length of Business Age (X4) and Accounting Training (X5) have a significant negative effect on the use of information accounting in MSMEs, South Pekalongan District, Pekalongan City.